Hyperpolarized 13C NMR studies of glucose metabolism in living breast cancer cell cultures. (24th September 2013) - Harris, T.; Degani, H.; Frydman, L.
<x xml:space="preserve">Abstract</x> The recent development of dissolution dynamic nuclear polarization (DNP) gives NMR the sensitivity to follow metabolic processes in living systems with high temporal resolution. In this article, we apply dissolution DNP to study the metabolism of hyperpolarized U‐13C, 2H7‐glucose in living, perfused human breast cancer cells. Spectrally selective pulses were used to maximize the signal of the main product, lactate, whilst preserving the glucose polarization; in this way, both C1‐lactate and C3‐lactate could be observed with high temporal resolution. The production of lactate by T47D breast cancer cells can be characterized by Michaelis–Menten‐like kinetics, with Km = 3.5 ± 1.5 mm and Vmax = 34 ± 4 fmol/cell/min. The high sensitivity of this method also allowed us to observe and quantify the glycolytic intermediates dihydroxyacetone phosphate and 3‐phosphoglycerate. Even with the enhanced DNP signal, many other glycolytic intermediates could not be detected directly. Nevertheless, by applying saturation transfer methods, the glycolytic intermediates glucose‐6‐phosphate, fructose‐6‐phosphate, fructose‐1, 6‐bisphosphate, glyceraldehyde‐3‐phosphate, phosphoenolpyruvate and pyruvate could be observed indirectly. This method shows great promise for the elucidation of the distinctive metabolism and metabolic control of cancer cells, suggesting multiple ways whereby hyperpolarized U‐13C, 2H7‐glucose NMR could aid in the diagnosis and characterization of cancer in vivo. Copyright © 2013 John Wiley & Sons, Ltd.